Do Aid Donors Coordinate Within Recipient Countries? - Hannes Öhler (University of Heidelberg, Department of Economics, 2013)
Aid fragmentation and a lack of donor coordination have been widely recognized as principal problems impairing the effectiveness of aid. In particular, the importance of within-country division of labor has been highlighted in recent years. At the same time, rigorous quantitative analyses of within-country aid coordination are largely missing. Taking the whole donor pool(including NGOs) within an aid recipient country into account, we examine the coordination behavior of donors across regions and sectors. Our results indicate a modest degree of donor coordination within Cambodia, even after the 2005 Paris Declaration. In particular, the coordination efforts among bilateral donors seem rather limited, suggesting that their political and economic interests prevent closer coordination. With respect to the behavior of NGOs, we find them to be mainly active in the same regions and sectors as official donors, creating coordination problems between the two groups of donors. In addition, NGOs appear to cluster in the regional-sectoral space although there seems to be some sort of coordination among them.
urn:nbn:de:bsz:16-heidok-143724
Keywords: 330; donor coordination; bilateral donors; multilateral donors; international NGOs; national NGOs; Cambodia